2018
DOI: 10.3329/bccj.v6i1.36602
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive protein in hypertension as a cardiovascular risk factor: A prospective observational study

Abstract: Background and objective : C-reactive protein (CRP) is a well-known inflammatory biomarker and is associated with cardiovascular risk. Our objective was to see whether it is also associated with hypertension and its complications.Methodology : This prospective observational study was carried out in general outpatient department (OPD) of a tertiary level hospital on a total of 112 patients, among them 71 were hypertensive and 41 were normotensive. Baseline CRP was measured in all subjects and followed them up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The current study also found that median values of CRP were significantly elevated in cases compared to controls (P <.001). These results concur with results from previous studies [31][32]. However, another older study by Sesso and others reported that CRP was not associated with higher risk of developing hypertension in middle-aged and older men [33].…”
Section: Discussionsupporting
confidence: 92%
“…The current study also found that median values of CRP were significantly elevated in cases compared to controls (P <.001). These results concur with results from previous studies [31][32]. However, another older study by Sesso and others reported that CRP was not associated with higher risk of developing hypertension in middle-aged and older men [33].…”
Section: Discussionsupporting
confidence: 92%
“…Ethnic group differences were evident in detecting the association of CRP levels with hypertension [71]. No correlation was found between CRP and hypertension levels in Bangladeshi [72], and Chinese participants, except Hispanic participants [73]. A study showed that an increased CRP level would not result in a higher CKD risk [74].…”
Section: Plos Onementioning
confidence: 99%